Phenethylamine in chlorella alleviates high-fat diet-induced mouse liver damage by regulating generation of methylglyoxal - Yifeng Zheng (Nature Portfolio, 2021)
Abstract This study examined the effects of oral administration of water extract of chlorella (WEC) (100 mg/kg bodyweight) and phenethylamine (10 μg/kg bodyweight) on high-fat diet (HFD)-induced liver damage in mice. Phenethylamine significantly mitigated HFD-induced lipid oxidation (generation of malondialdehyde) and liver damage without markedly decreasing hepatic lipid accumulation. WEC exerted similar effects although with decreased efficacy. In addition, WEC and phenethylamine decreased the methylglyoxal levels and increased the glyceraldehyde 3-phosphate dehydrogenase (GAPDH) protein levels in the liver. Methylglyoxal is generated from substrates of GAPDH, dihydroxyacetone phosphate and glyceraldehyde 3-phosphate. These facts indicate that methylglyoxal triggers oxidation of accumulated lipid, which generates malondialdehyde and consequently induces liver damage. Suppression of generation of toxic aldehydes by WEC and phenethylamine was also confirmed by maintaining hepatic cysteine, highly reactive to aldehydes. Thus, trace amounts of phenethylamine alleviate HFD-induced liver damage by regulating methylglyoxal via increase of GAPDH.